2011
DOI: 10.1021/op200181f
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Synthesis of (S,S)-Reboxetine Succinate: A Journey To Find the Cheapest Commercial Chemistry for Manufacture

Abstract: The development of a synthetic process for (S,S)-reboxetine succinate, a candidate for the treatment of fibromylagia, is disclosed from initial scale-up to deliver material for registrational stability testing through to commercial route evaluation and subsequent nomination. This entailed evaluation of several alternative routes to result in what would have been a commercially attractive process for launch of the compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…In a study by Hayes et al, authors reported an improved commercial-scale synthesis route for (S,S)-reboxetine succinate, a noradrenergic anti-depressant for the treatment of fibromyalgia in the latter stages of development at Pfizer [35,36]. The production of reboxetine requires an acetylation of diol intermediate.…”
Section: Pharmaceuticals Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Hayes et al, authors reported an improved commercial-scale synthesis route for (S,S)-reboxetine succinate, a noradrenergic anti-depressant for the treatment of fibromyalgia in the latter stages of development at Pfizer [35,36]. The production of reboxetine requires an acetylation of diol intermediate.…”
Section: Pharmaceuticals Industrymentioning
confidence: 99%
“…However, conventional synthesis routes rely on classical chemical acetylation that suffers from di-acetylation and poor enantioselectivity, therefore generating considerable amounts of unwanted byproducts [2]. The proposed generation synthesis route successfully employed Candida antartica lipase B, an active, commercially available enzyme, for the highly enantioselective acetylation of diol intermediate [36]. The lipase-catalyzed process resulted in the selective mono-acetylation of diol intermediate with 98% regioselectivity and greater than 99% yield.…”
Section: Pharmaceuticals Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…[4] As an alternative, stoichiometric chiral acylating agents can be used for enantioselective amidation of racemic amines. Researchers, including Fu, [5] Mioskowski, [6] Atkinson, [7] and others, [8] have reported progress on such methods but their widespread use has been precluded by restricted substrate scope, inconvenient reaction procedures, and lengthy syntheses of the reagents.…”
mentioning
confidence: 99%
“…[1] Überraschenderweise sind enzymatische und andere katalytische Racematspaltungen dieser wichtigen Bausteine weniger fortgeschritten; [2,3] Stand der Technik bleibt die Auftrennung durch Bildung der diastereomeren Salze oder Racematspaltung durch Chromatographie mit chiraler stationärer Phase. [4] Alternativ kçnnen chirale Acylierungsmittel stçchiometrisch für die enantioselektive Amidierung von racemischen Aminen eingesetzt werden. Die Gruppen um Fu, [5] Mioskowski, [6] Atkinson [7] sowie weitere [8] haben über Fortschritte bei diesen Methoden berichtet, jedoch wurde deren weit verbreiteter Einsatz durch eine eingeschränkte Substratbreite, umständliche Reaktionsprotokolle und langwierige Synthesen der Reagentien limitiert.Wir haben kürzlich eine Methode für die katalytische kinetische Racematspaltung von cyclischen sekundären Aminen entwickelt, welche die In-situ-Erzeugung der chiralen O-Acylhydroxamsäure 1 beinhaltet.…”
unclassified